Safety and Efficacy of Stereotactic Body Radiotherapy for Stage I Non–Small-Cell Lung Cancer in Routine Clinical Practice: A Patterns-of-Care and Outcome Analysis - Guckenberger, Matthias; Allgäuer, Michael; Appold, Steffen; Dieckmann, Karin; Ernst, Iris; Ganswindt, Ute; Holy, Richard; Nestle, Ursula; Nevinny-Stickel, Meinhard; Semrau, Sabine; Sterzing, Florian; Wittig, Andrea; et al. (Journal of thoracic oncology, 2013)
To evaluate safety and efficacy of stereotactic body radiotherapy (SBRT) for stage I non–small-cell lung cancer (NSCLC) in a patterns-of-care and patterns-of-outcome analysis. The working group “Extracranial Stereotactic Radiotherapy” of the German Society for Radiation Oncology performed a retrospective multicenter analysis of practice and outcome after SBRT for stage I NSCLC. Sixteen German and Austrian centers with experience in pulmonary SBRT were asked to participate. Data of 582 patients treated at 13 institutions between 1998 and 2011 were collected; all institutions, except one, were academic hospitals. A time trend to more advanced radiotherapy technologies and escalated irradiation doses was observed, but patient characteristics (age, performance status, pulmonary function) remained stable over time. Interinstitutional variability was substantial in all treatment characteristics but not in patient characteristics. After an average follow-up of 21 months, 3-year freedom from local progression (FFLP) and overall survival (OS) were 79.6% and 47.1%, respectively. The biological effective dose was the most significant factor influencing FFLP and OS: after more than 106 Gy biological effective dose as planning target volume encompassing dose (N = 164), 3-year FFLP and OS were 92.5% and 62.2%, respectively. No evidence of a learning curve or improvement of results with larger SBRT experience and implementation of new radiotherapy technologies was observed. SBRT for stage I NSCLC was safe and effective in this multi-institutional, academic environment, despite considerable interinstitutional variability and time trends in SBRT practice. Radiotherapy dose was identified as a major treatment factor influencing local tumor control and OS.